Rational approach towards enhancing solar water splitting: a case study of Au-RGO/N-RGO-TiO2 - Bharad, Pradnya A.; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Nanoscale, 2015)
A rational approach was employed to enhance the solar water splitting (SWS) efficiency by systematically combining various important factors that helps to increase the photocatalytic activity. The rational approach includes four important parameters, namely, charge generation through simulated sunlight absorption, charge separation and diffusion, charge utilization through redox reaction, and the electronic integration of all of the above three factors. The complexity of the TiO2 based catalyst and its SWS activity was increased systematically by adding reduced graphene oxide (RGO) or N-doped RGO and/or nanogold. Au-N-RGO-TiO2 shows the maximum apparent quantum yield (AQY) of 2.46% with a H-2 yield (525 mu mol g(-1) h(-1)) from aqueous methanol, and overall water splitting activity (22 mu mol g(-1) h(-1); AQY = 0.1%) without any sacrificial agent under one sun conditions. This exercise helps to understand the factors which help to enhance the SWS activity. Activity enhancement was observed when there is synergy among the components, especially the simulated sunlight absorption (or one sun conditions), charge separation/conduction and charge utilization. Electronic integration among the components provides the synergy for efficient solar light harvesting. In our opinion, the above synergy helps to increase the overall utilization of charge carriers towards the higher activity.